Religious Moderation In Sayyid Quṭb’s Tafsir - Fathollah, Moh. Fauzan; Azizah, Imroatul; Thobroni, Ahmad Yusam; Hamzah, Moh. (Jurnal Ushuluddin, 2025)
One comprehensive commentary on religious moderation is Tafsīr Fī Ẓilāl al-Qurʾān by Sayyid Quṭb. However, this interpretation often faces negative stigma from certain groups who perceive it as radical and extreme. Previous studies have examined Sayyid Quṭb's ideas within the context of Islamic politics and the Islamist movement, but research that situates his thoughts within the framework of maqāṣid al-sharīʿah remains limited. In this regard, the maqāṣid asy-syarī’ah approach developed by al-Shāṭibī offers a more inclusive perspective for understanding the concept of moderation in the Qur'an and its application in contemporary life. This research employs a maqāṣid al-sharīʿah approach using qualitative methods. The analysis technique utilized refers to the theory of Miles and Huberman. The results of this research indicate that wasāṭiyyah plays a crucial role in preventing extreme attitudes, both in the form of extremism and liberalism, which can disrupt individual and social balance. Maqāṣid asy-syarī'ah emerged as a new methodology that has produced the Fiqh Ijtihādī and Fiqh Maqāṣidī approaches. Through this concept, Asy-Syāṭibī emphasized that the primary aim of Islamic law is to create benefits and promote good values in every implementation. Wasāṭiyyah, from the maqāṣid perspective, provides an adaptive framework for Muslims, ensuring that Islamic law remains relevant to various social, economic, and political situations. With the guidance of maqāṣid, moderation in Islam becomes the foundation for living harmoniously in a pluralistic society, where justice, tolerance, and benefit are the main priorities